Pertanggungjawaban Pejabat Pembuat Akta Tanah Terhadap Keabsahan Akta Jual Beli - Adistia, Meisya (UNES Law Review, 2024)
Certificates serve as proof of ownership of land registered with authorized PPAT approval, PPAT makes the original act for legal process, land can be transferred from one party to another through the process of purchase, sale, or inheritance. PPAT makes the act as proof of the implementation of legal activity related to a particular land. It is very important for PPAT to consider the components involved in making the PPAT act. Although PPAT may experience errors or inaccuracies in the process of making the act, therefore PPAT should be legally liable, and if proved guilty PPAT must be responsible, deliberately or not, legal consequences can be imposed on PPAT based on the degree of inexactitude or error in the sale and sale act made by PPAT. Based on this, the author is interested to raise this issue in a study entitled Responsibility of the Land Act Maker Officer to the validity of the Sale and Sale of Land Act. This research is focused on the type of normative research, i.e. legal research in which data collection is carried out using library research, data collected is analyzed using qualitative analysis described descriptively analytically. PPAT has full responsibility for the Sale and Purchase Act it makes, but if the fault lies on the other party then this is not part of PPAT's responsibility.